Does Culture, Motivation, Competence, Leadership, Commitment Influence Quality Performance? - Agus Purwanto; Masduki Asbari; Priyono Budi Santoso (Politeknik Negeri Bengkalis, 2019)
The purpose of this study is to analyze the influence of leadership, motivation, competence, commitment, and organizational culture on the implementation performance of the Quality Performance at a packaging manufacturing industry. The study sample as population is all 300 employees of packaging industry. The analysis of this study uses SEM (Structural Equation Model) with LISREL software program version 8.70. The results show that leadership and organizational culture have significant influence on the implementation performance of quality management system, while motivation, competence and commitment do not affect the implementation performance of the quality management system.